Anchor institutions and small firms in the UK : a review of the literature on anchor institutions and their role in developing management and leadership skills in small firms /: a review of the literature on anchor institutions and their role in developing management and leadership skills in small firms. (2015) - Smallbone, David; Kitching, John, 1964-; Blackburn, Robert A, 1957-; Mosavi, Sara
No abstract available